2018
DOI: 10.1194/jlr.m082099
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated Angptl8 knockout suppresses plasma triglyceride concentrations and adiposity in rats

Abstract: Angiopoietin-like protein (ANGPTL)8 is a liver- and adipocyte-derived protein that controls plasma triglyceride (TG) levels. Most animal studies have used mouse models. Here, we generated an KO rat model using a clustered regulatory interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) (CRISPR/Cas9) system to clarify the roles of ANGPTL8 in glucose and lipid metabolism. Compared with WT rats, KO rats had lower body weight and fat content, associated with impaired lipogenesis in adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Representative fat pads from 12-week-old male mice are shown in Figure 2A. The epididymal (Epi) fat pads from the A8 -/mice were visibly smaller and weighed significantly less than those from WT animals ( Figure 2B), which is consistent with what was seen in the A3 -/-A8 -/mice (28) and the A8 -/rat (30). The weights of the WAT-subcutaneous (SQ) fat were also lower in the A8 -/mice.…”
Section: Introductionsupporting
confidence: 79%
“…Representative fat pads from 12-week-old male mice are shown in Figure 2A. The epididymal (Epi) fat pads from the A8 -/mice were visibly smaller and weighed significantly less than those from WT animals ( Figure 2B), which is consistent with what was seen in the A3 -/-A8 -/mice (28) and the A8 -/rat (30). The weights of the WAT-subcutaneous (SQ) fat were also lower in the A8 -/mice.…”
Section: Introductionsupporting
confidence: 79%
“…The relationship between ANGPTL8 and triglyceride has also been deeply excavated. A recently published paper reported that ANGPTL8 knockout mediated by CRISPR-Cas9 system led to reduced plasma triglyceride levels [ 26 ], which verified conclusions from animal experiments—ANGPTL8 was found to inhibit LPL activity and elevate plasma triglyceride partly via ANGPTL3 activation after feeding [ 14 ]. A prospective cohort study conducted in Korean children revealed that baseline ANGPTL8 was associated with future changes in triglyceride levels [ 27 ].…”
Section: Discussionsupporting
confidence: 53%
“…The association of ANGPTL8 with insulin resistance [18,26,27], blood glucose [28,29], C-peptide and glycosylated haemoglobin (HbA1C) have not offered clear results [30]. In animals, a positive correlation of circulating ANGPTL8 with triglyceride levels exists [10,[31][32][33]. These facts were also confirmed in humans [34].…”
Section: Introductionmentioning
confidence: 99%